(untitled) (ACTA MEDICA PERUANA, 2024)
In the present paper, the authors review the pathogenic mechanisms in the development of osteoarthritis. This review also discuss the morfologic and metabolic changes in the articular cartilage and the rol of differents mediators and hormones in this disease.